Noise induced hearing loss among the textile industry workers (Bangladesh Journal of Otorhinolaryngology, 2009)
Noise is one of the common physical environmental hazard in the workplace. A study was carried out in a textile industry at Gazipur from July 2004 to December 2004 to find out the prevalence, types and severity of hearing loss among the workers. The sample size was 97 and the total number of workers was 1900. Out of 97 sample, 26 workers were having noise induced hearing loss (NIHL). The incidence of NIHL was 20.59% in workers aged less than 35 years and 41.38%. in workers aged above 35 years Among the departments of factory, highest noise level was in generator department (96-100 dB). In generator department, 46.67% workers had the hearing loss. Overall, the prevalence of NIHL among textile workers of the study place was 33.46%. Key words: Noise, NIHL, industrial workers.DOI: 10.3329/bjo.v14i2.3279 Bangladesh J of Otorhinolaryngology 2008; 14(2) : 39-45